Preparation method and application of composite sponge for efficiently capturing copper ions

Through the composite sponge material prepared with agricultural and forestry waste as the substrate, alkali treatment, acid treatment, ultrasonic dispersion and chemical crosslinking are used to form a three-dimensional porous structure rich in heavy metal chelating groups such as amino groups and carboxyl groups, solving the problems of high energy consumption and difficulty in separation and regeneration of existing adsorbents when treating heavy metal-containing wastewater, achieving the effect of efficiently trapping copper ions and reducing the cost of water treatment.

CN115920857BActive Publication Date: 2025-03-14YILI NORMAL UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211538443.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-01
Publication Date
2025-03-14
Estimated Expiration
2042-12-01

AI Technical Summary

Technical Problem

When treating heavy metal-containing wastewater, existing adsorbents have problems such as high energy consumption in the production process, difficulty in separation and regeneration after adsorption, and the production process of traditional activated carbon is unsustainable.

Method used

The composite sponge material prepared with agricultural and forestry waste as the substrate is used to form a three-dimensional porous structure rich in heavy metal chelating groups such as amino groups and carboxyl groups through alkali treatment, acid treatment, ultrasonic dispersion and chemical crosslinking, and improve its adsorption and separation performance on copper ions.

Benefits of technology

It has achieved efficient capture of copper ions in aqueous solution, and is easy to separate and regenerate after adsorption, which reduces the cost of water treatment and conforms to the concept of sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115920857B_ABST
    Figure CN115920857B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method and application of a composite sponge for efficiently capturing copper ions. The sponge material is based on discarded or low-value rice straw, wheat straw, corn straw, fruit peel, bentonite, added with composite material starch, cyclodextrin, sodium alginate or chitosan, chemically cross-linked with epichlorohydrin, glutaraldehyde or calcium chloride, and prepared by freeze-drying. The adsorbent substrate is made of waste materials for waste treatment, which is low-carbon and environmentally friendly, and the preparation process is simple. The synthesized composite sponge has a regular three-dimensional interpenetrating porous network structure, excellent mechanical properties, high water stability, good selective removal effect of copper ions, and easy to regenerate and reuse after adsorption. Overall, its development provides a direction for the resource utilization of discarded agricultural and forestry wastes, and also provides a new idea for the development and exploration of adsorbents for the enrichment and recovery of heavy metals in water bodies, and has great development potential and practical value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of heavy metal treatment-adsorption materials in water bodies, and in particular relates to a preparation method and application of a composite sponge for efficiently capturing copper ions. Background Art

[0002] The contradiction between China's water shortage and water pollution caused by industrial and agricultural development and urbanization has intensified, especially heavy metal-contaminated wastewater from metallurgical machinery manufacturing, electronic instrument processing, paper printing and mineral mining. Although potassium, calcium, sodium, magnesium, iron, chromium, manganese, copper, zinc, cobalt, molybdenum, tin and vanadium are essential trace elements for the human body, excessive heavy metal elements are non-biodegradable and easily accumulate in organisms, posing serious health risks to humans and potentially negative impacts on natural ecosystems. For example, although Cu(Ⅱ) is an essential trace element for the human body, if exposed to an environment with excessive discharge, it can also cause serious health problems, such as Menkes disease, Wilson disease, Alzheimer's disease, etc. Therefore, efficient remediation of water bodies contaminated by heavy metals is one of the important ways to alleviate the contradiction between water shortage and water pollution.

[0003] At present, the technical methods for remediating polluted water bodies include chemical precipitation, membrane separation, ion exchange, electrolysis, biological method and adsorption. Among them, the adsorption method has attracted much attention due to its simple operation, excellent adsorption performance and economic applicability. The principle of using the adsorption method to treat heavy metal-containing wastewater is to use the surface functional groups of the adsorbent material and the high specific surface area advantage of the material to adsorb pollutants such as heavy metal ions in the water body onto the material, thereby achieving the purpose of completely removing pollutants from the water body. This process can achieve the purpose of enriching, removing and recovering heavy metals. Moreover, since the adsorbent can be regenerated and recycled, it also has the advantages of easy separation and regeneration and no secondary pollutants such as sludge. The production process of traditional and widely used activated carbon is considered unsustainable due to its high energy consumption in the production process and the emission of greenhouse gas carbon dioxide. In addition, some adsorbents exist in the form of powder or nanoparticles. Although the adsorption efficiency is high, there is a defect that the adsorbent is difficult to separate / regenerate after adsorption. Therefore, it is urgent to develop new adsorbents with low cost, high adsorption efficiency and easy separation and regeneration after adsorption. my country has abundant resources of agricultural and forestry wastes such as straw, wheat straw, corn straw, and fruit peels (grapefruit peel, banana peel, orange peel), but they have not been recycled and utilized at a high value, resulting in a huge waste of resources. Agricultural and forestry wastes are also called wood cellulose. Their structure is rich in heavy metal chelating groups such as hydroxyl, carboxyl, methoxy, and phenolic hydroxyl groups. They are green, natural, and pollution-free substrates for preparing heavy metal adsorbents. To a certain extent, they can achieve waste treatment, promote waste recycling, and achieve the purpose of low-carbon energy conservation and consumption reduction, which is in line with the concept of sustainable development. The pure agricultural and forestry waste sponge material prepared with agricultural and forestry waste as the substrate has low copper ion capture performance, and because of its rich hydroxyl groups in the structure itself, it is easy to form hydrogen bonds with water molecules and undergo physical crosslinking, but the bond structure formed by physical crosslinking is unstable, resulting in its instability in aqueous solution and easy to dissociate and disperse in aqueous solution. Therefore, it is necessary to introduce a matrix or crosslinker rich in amino, carboxyl, epoxy, hydroxyl, or aldehyde groups to form a stronger bond structure with it for chemical composite crosslinking to increase its stability in aqueous solution. Starch, sodium alginate, cyclodextrin, bentonite or chitosan are also natural polymer compounds widely distributed in nature, especially chitosan, whose reserves are second only to cellulose. The surfaces of these polymer compounds are rich in amino, carboxyl, hydroxyl and other heavy metal chelating groups. The sponge materials prepared by compounding with agricultural and forestry wastes have a three-dimensional interpenetrating porous network structure inside, which can achieve efficient removal of copper ions and are easy to separate and regenerate after separation, saving water treatment costs.

[0004] The development of this sponge material provides a direction for the resource utilization of abandoned agricultural and forestry wastes, and also provides new ideas for the development and exploration of adsorbents for the enrichment and recovery of heavy metals in water bodies. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method and application of a composite sponge for efficiently capturing copper ions, so as to solve the problems raised in the above background technology.

[0006] In order to solve the above technical problems, the technical solution provided by the present invention is: a method for preparing a composite sponge for efficiently capturing copper ions, the steps of which are as follows:

[0007] (1) drying the collected discarded rice straw, wheat straw, corn straw and fruit peel at 30°C, crushing, grinding and sieving through 40-100 mesh;

[0008] (2) placing the finished product of (1) into a container, adding sodium hydroxide for alkali treatment at 50-80°C, mechanically stirring, washing the solid residue with ultrapure water until neutral, and drying at 50-80°C;

[0009] (3) placing the alkali-treated substrate of (2) into a container, adding hydrochloric acid at 50-80° C. for acid treatment and mechanical stirring, washing the solid residue with ultrapure water until neutral, drying at 50-80° C. for later use;

[0010] (4) placing the pretreated substrate prepared in (3) into a container, adding bentonite and 30-50 ml of water, and dispersing evenly by ultrasonication for later use;

[0011] (5) dissolving starch, sodium alginate, cyclodextrin or chitosan with calcium chloride, water or glacial acetic acid solution to prepare a 2-6 wt % solution for later use;

[0012] (6) Add 40-60 ml of solution (5) to (4), stir mechanically at room temperature for 30 min, add epichlorohydrin, glutaraldehyde, calcium chloride and 2.5% polyvinyl alcohol, and continue stirring for 1-3 h until the solution becomes a homogeneous and thick gel;

[0013] (7) Pour the colloid obtained in (6) into a mold, place it in a -50°C ultra-low temperature refrigerator for pre-freezing for 30-60 minutes, take it out, and place it in a freeze dryer for freeze drying to obtain a composite sponge.

[0014] As a preferred embodiment, the mass ratio of the solid prepared in (3) to the bentonite in step (4) is 2:1 to 1:2.

[0015] As a preferred embodiment, the fruit peel in step (1) is at least one of grapefruit peel, banana peel and orange peel.

[0016] The composite sponge for efficiently capturing copper ions is characterized in that it efficiently captures divalent copper ions Cu in aqueous solution. 2 + .

[0017] The advantages of the present invention are:

[0018] 1. The composite sponge for efficiently capturing copper ions of the present invention has a simple preparation process, a base material with a wide range of sources, is inexpensive and easily available, and can treat waste with waste, thereby achieving the reduction, reuse and recycling of agricultural and forestry wastes, and conforming to the sustainable development concept of green, low-carbon, energy-saving and consumption-reducing.

[0019] 2. The present invention provides a method for preparing a composite sponge for efficiently capturing copper ions. The wood cellulose sponge prepared by chemical cross-linking in step (6) has high water stability in aqueous solution, has high selective adsorption for copper ions, is easy to separate and regenerate after adsorption, does not cause secondary pollution to the water body, and effectively saves water treatment costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Digital images of sponges prepared for three different lignocellulose addition ratios;

[0021] Figure 2 Effect of pH and Zeta potential on the adsorption of Cu by lignocellulose composite sponge 2+ The impact of

[0022] Figure 3 The adsorption kinetics data, adsorption kinetics data fitting curve and intra-particle diffusion model of lignocellulose composite sponge are shown;

[0023] Figure 4 The adsorption isotherm data of the wood cellulose composite sponge and the adsorption isotherm data fitting curve diagram;

[0024] Figure 5 The adsorption diagram of each metal ion by lignocellulose composite sponge in single and mixed systems;

[0025] Figure 6 is the graph of copper adsorption in each regeneration cycle of lignocellulose composite sponge;

[0026] Figure 7 Cu adsorption for lignocellulose composite sponge 2+ Before and after comparison pictures. DETAILED DESCRIPTION

[0027] The present invention is described below with specific embodiments, but is not intended to be limiting of the present invention.

[0028] Embodiment 1

[0029] (1) collecting discarded rice straw, wheat straw, corn straw, and fruit peels (grapefruit peel, banana peel, and orange peel) and drying them at low temperature (30° C.), crushing, grinding, and sieving (40-100 mesh);

[0030] (2) placing (1) in a container, adding sodium hydroxide for alkali treatment and mechanical stirring (50-80° C.), washing the solid residue with ultrapure water until neutral, and drying (50-80° C.);

[0031] (3) placing the alkali-treated substrate of (2) into a container, adding hydrochloric acid for acid treatment with mechanical stirring (50-80° C.), washing the solid residue with ultrapure water until neutral, drying at low temperature (50-80° C.), and setting aside;

[0032] (4) placing the pretreated substrate prepared in (3) into a container, adding bentonite and water (30-50 ml), and dispersing evenly by ultrasonication for later use;

[0033] (5) dissolving starch, sodium alginate, cyclodextrin or chitosan with calcium chloride, water or glacial acetic acid solution to prepare a 2-6 wt % solution for later use;

[0034] (6) Add solution (5) (40-60 ml) to (4), stir mechanically at room temperature for 30 min, add epichlorohydrin, glutaraldehyde, calcium chloride and polyvinyl alcohol (2.5%), and continue stirring for 1-3 h until the solution becomes a homogeneous and thick gel;

[0035] (7) The colloid obtained in (6) was poured into a mold, placed in an ultra-low temperature refrigerator (-50°C) for pre-freezing for 30-60 min, taken out, and placed in a freeze dryer for freeze drying to obtain composite sponges, which were recorded as LCB-1, LCB-2 and LCB-3.

[0036] Figure 1 Digital images and scanning electron microscope images of sponges prepared with three different proportions of lignocellulose addition. As can be seen from the figure, from LCB-1 to LCB-3, the lignocellulose content gradually increases, the bentonite content gradually decreases, and the pores inside the sponge become finer and denser, while the mechanical strength of the pores gradually becomes weaker. Generally, the smaller the pores, the larger the specific surface area, and the better the effect of adsorption and removal of copper ions.

[0037] Figure 2 Effect of pH and Zeta potential on the adsorption of Cu by lignocellulose sponge 2+ The pH of LCB-1, LCB-2 and LCB-3 PZC The values ​​of pH were 2.10, 3.22 and 3.71 respectively. This trend was positively correlated and negatively correlated with the contents of lignocellulose and bentonite in LCB, respectively. The more lignocellulose and the less bentonite in the system, the higher the pH value. PZC The larger the solution pH, the smaller the negative charge. PZC When LCB-1, LCB-2 and LCB-3 have negative charges on their surfaces, it is beneficial to the positively charged Cu 2+Electrostatic adsorption / chemical chelation removal. The removal rate of Cu(Ⅱ) by the three composite sponges gradually increased with the increase of pH, reaching the maximum value at pH = 5.5. LCB-2 had the best adsorption and removal effect on Cu(Ⅱ) ions, with a final C / C0 of 0.073.

[0038] Figure 3 The adsorption isotherm data of wood cellulose sponges with different proportions and the adsorption isotherm data fitting curves. (ac) and (df) are the Langmuir and Freundlich fitting curves of LCB-1, LCB-2 and LCB-3 after the adsorption isotherm data of copper ions were fitted. The experimental conditions were that the composite sponge weighed 20 mg, the concentration and volume of the added copper solution were 1-1000 mg / L and 20 mL, the pH of the copper solution was 5.5, the reaction temperature was 30 ° C, and the reaction time was 240 min. Freundlich model (R 2 LCB-1 =0.957,R 2 LCB-2 =0.986,R 2 LCB-3 =0.994) than the Langmuir model (R 2 LCB-1 =0.692,R 2 LCB-2 =0.921,R 2 LCB-3 =0.859) can better describe the adsorption process of Cu(II) on the composite sponge, indicating that the adsorption of Cu(II) ions on the heterogeneous surface of the composite sponge is a multilayer homogeneous adsorption process. The Langmuirs isotherm q of LCB-2 m Reach 1468mg / g(R 2 =0.921), which is much higher than the experimental value (861.58 mg / g), indicating that LCB-2 has a huge adsorption and removal potential for the capture of Cu(II), which is beneficial to its practical application.

[0039] Figure 4 The adsorption kinetics of lignocellulose sponge is fitted. Specifically, (af) are the fitting curves of pseudo-first-order and pseudo-second-order kinetic models. The experimental conditions are that the composite sponge weighs 20 mg, the concentration and volume of the copper solution added are 10 mg / L / 400 mg / L and 20 mL, respectively, the pH of the copper solution is 5.5, the reaction temperature is 30 ° C, and the reaction time is 1-240 min. Under the experimental conditions of 10 mg / L and 400 mg / L, LCB-2 has a good adsorption performance on Cu 2+The maximum adsorption capacity is 9.2 and 378.4 mg / g; in the fitting curve, the adsorption of copper by LCB-2 is more consistent with the pseudo-second-order kinetic equation, and the corresponding maximum adsorption capacities are 9.3 and 364.0 mg / g, which are close to the experimental values. This shows that the LCB composite sponge is suitable for the remediation of low-concentration copper-contaminated water bodies and for the efficient removal of copper ions in high-concentration industrial wastewater.

[0040] Figure 5 This is the adsorption diagram of cellulose sponge for various metal ions in single and mixed systems. It can be seen from the figure that no matter in a single heavy metal system or in a mixed system of two heavy metals, the composite sponge shows a much higher selective adsorption rate for copper than other ions, which shows that the composite sponge has a high efficiency in selective removal of copper ions.

[0041] Figure 6 This is a comparison chart of the adsorption amount of copper ions in each recycling process of wood cellulose sponge. It can be seen from the figure that after 6 cycles of adsorption and desorption, the removal rate of copper ions by the composite sponge only decreased by 5.3%, indicating that the composite sponge has excellent regeneration adsorption performance, can effectively remove pollutants in water and effectively reduce water treatment costs, and is suitable for practical promotion and application.

[0042] Figure 7 This is a comparison chart of the wood cellulose sponge before and after adsorption. It can be seen that the composite sponge has been floating on the water surface during the adsorption process, efficiently enriching the copper ions in the water. After treatment, it can be quickly salvaged and removed, achieving rapid separation after adsorption and improving the actual water treatment effect.

[0043] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a composite sponge for efficiently capturing copper ions, characterized in that: The steps are as follows: (1) drying the collected discarded rice straw, wheat straw, corn straw and fruit peel at 30°C, crushing, grinding and sieving through 40-100 mesh; (2) placing the finished product of (1) into a container, adding sodium hydroxide for alkali treatment at 50-80°C, mechanically stirring, washing the solid residue with ultrapure water until neutral, and drying at 50-80°C; (3) placing the alkali-treated substrate of (2) into a container, adding hydrochloric acid at 50-80° C. for acid treatment and mechanical stirring, washing the solid residue with ultrapure water until neutral, drying at 50-80° C. for later use; (4) placing the pretreated substrate prepared in (3) into a container, adding bentonite and 30-50 ml of water, and dispersing evenly by ultrasonication for later use; (5) dissolving starch, sodium alginate, cyclodextrin or chitosan with calcium chloride, water or glacial acetic acid solution to prepare a 2-6 wt % solution for later use; (6) Add 40-60 ml of solution (5) to (4), stir mechanically at room temperature for 30 min, add epichlorohydrin, glutaraldehyde, calcium chloride and 2.5% polyvinyl alcohol, and continue stirring for 1-3 h until the solution becomes a homogeneous and thick gel; (7) Pour the colloid obtained in (6) into a mold, place it in a -50°C ultra-low temperature refrigerator for pre-freezing for 30-60 minutes, take it out, and place it in a freeze dryer for freeze drying to obtain a composite sponge.

2. The method for preparing a composite sponge for efficiently capturing copper ions according to claim 1, characterized in that: In the step (4), the mass ratio of the solid prepared in (3) to the bentonite is 2:1 to 1:

2.

3. The method for preparing a composite sponge for efficiently capturing copper ions as claimed in claim 1, characterized in that: The fruit peel in step (1) is at least one of grapefruit peel, banana peel and orange peel.

4. The method for preparing the composite sponge for efficiently capturing copper ions as claimed in claim 1, wherein the composite sponge is used to efficiently capture divalent copper ions in aqueous solution.

Citation Information

Patent Citations

  • Mercury ion rapidly absorbing composite sponge absorbent and preparation and application methods thereof

    CN109364894A

  • Plant cellulose absorption sponge, and preparation method and application of plant cellulose absorption sponge

    CN110354819A